2022
DOI: 10.3389/fnins.2022.964715
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer in frontotemporal lobar degeneration and amyotrophic lateral sclerosis

Abstract: PurposeTauopathy and transactive response DNA binding protein 43 (TDP-43) proteinopathy are associated with neurodegenerative diseases. These proteinopathies are difficult to detect in vivo. This study examined if spectral-domain optical coherence tomography (SD-OCT) can differentiate in vivo the difference in peripapillary retinal nerve fibre layer (pRNFL) thickness and macular retinal thickness between participants with presumed tauopathy (progressive supranuclear palsy) and those with presumed TDP-43 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Only one study has compared ocular changes between patients with a tauopathy (i.e., progressive supranuclear palsy) and patients with a transactive response DNA binding protein 43 (TDP-43) proteinopathy (i.e., ALS and frontotemporal dementia). 27 Those authors found that the peripapillary RNFL in the temporal sector was significantly thinner in the TDP-43 than the tauopathy patients prior to correcting for multiple comparisons.…”
Section: Discussionmentioning
confidence: 98%
“…Only one study has compared ocular changes between patients with a tauopathy (i.e., progressive supranuclear palsy) and patients with a transactive response DNA binding protein 43 (TDP-43) proteinopathy (i.e., ALS and frontotemporal dementia). 27 Those authors found that the peripapillary RNFL in the temporal sector was significantly thinner in the TDP-43 than the tauopathy patients prior to correcting for multiple comparisons.…”
Section: Discussionmentioning
confidence: 98%